Education Coverage in Television News: A Typology and Analysis of 35 Years of Topics - Kevin Coe; Paul J. Kuttner (SAGE Publishing, 2018)
News media play a significant role in the education policy arena, informing the public about pressing issues and influencing how such issues are prioritized and understood. For this reason, researchers are increasingly raising concerns about how much attention news media give to education, which topics are covered, and how topics are addressed. In this article, the authors advance this growing body of research through a quantitative content analysis of the topics in national television news coverage of pre-K-12 (early childhood through high school) education in the United States over the past 35 years. The authors present their typology of education topics, providing a foundation for future research in this area, and analyze major trends. This article also serves as an introduction to a new data set: 2,322 abstracts, representing all substantial education news coverage from the three major evening news networks, included as an online appendix.